2002
DOI: 10.1007/bf00766646
|View full text |Cite
|
Sign up to set email alerts
|

Sinapyl alcohol-specific peroxidase isoenzyme catalyzes the formation of the dehydrogenative polymer from sinapyl alcohol

Abstract: Two peroxidases, CWPO-A and CWPO-C, were isolated from the cell walls of poplar (Populus alba L.) callus culture. The cationic CWPO-C showed a strong preference for sinapyl alcohol over coniferyl alcohol as substrate. Thus, the monolignol utilization of CWPO-C is unique compared with other peroxidases, including anionic CWPO-A and horseradish peroxidase (HRP). CWPO-C polymerized oligomeric sinapyl alcohol (S-oligo) and sinapyl alcohol, producing a polymer of greater molecular weight. In contrast, HRP, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 26 publications
3
50
0
1
Order By: Relevance
“…In this regard, we previously reported that a peroxidase isoenzyme, CWPO-C, oxidizes both monolignols and synthetic high molecular weight lignin. Its enzymatic characteristics strongly support that CWPO-C is a lignification specific peroxidase (Sasaki et al 2004;Aoyama et al 2002).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In this regard, we previously reported that a peroxidase isoenzyme, CWPO-C, oxidizes both monolignols and synthetic high molecular weight lignin. Its enzymatic characteristics strongly support that CWPO-C is a lignification specific peroxidase (Sasaki et al 2004;Aoyama et al 2002).…”
Section: Discussionmentioning
confidence: 79%
“…The callus was maintained on the medium at 25°C in the dark. Peroxidase isoenzyme (CWPO-C) was purified from poplar callus as described by Aoyama et al (Aoyama et al 2002). The poplar tree (P. alba) was grown in Kyushu University and used for experiments of CWPO-C cloning, transcript, and localization analysis.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…An unique peroxidase isoenzyme from poplar callus, cationic cell-wall-bound peroxidase (CWPO-C), has broad substrate versatility and was reported to use sinapyl alcohol 2 and syringaldazine 6 as preferred substrates (Tsutsumi et al, , 1998Aoyama et al, 2002;Sasaki et al, 2004). Furthermore, CWPO-C catalyzes the oxidation of synthetic lignin polymers and ferrocytochrome c, unlike other plant peroxidases (Sasaki et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, cationic cell wall-bound peroxidase (CWPO-C) from poplar could catalyze the oxidation of sinapyl alcohol as preferred substrate [17][18][19][20][21]. Furthermore, CWPO-C could catalyze oxidation of synthetic lignin polymers and ferrocytochrome c, unlike other plant peroxidases [21].…”
Section: Introductionmentioning
confidence: 99%